You are on page 1of 5

GITIMH3 94107 Integration Page 1

Approximation Methods
 Integration is the process of calculation the area of a region under a curve.

The Trapezoidal Rule:


 An approximate area under the curve is found by finding the area of trapeziums.
b


ba
Equation: f  x dx   y 0  y n  2 y 1  y 2  ...  y n 1 
a 2.n
n = Number of subintervals (or n + 1 function values)

f(x)

y0 yn

a b

Simpson’s Rule:
 An approximate area under the curve is found by finding the area under parabolic
arcs.
b


ba
Equation: f  x dx   y 0  y n  4  y 1  y 3  ...  2 y 2  y 4  ...
a 3.n
n = Number of subintervals (or n + 1 function values)

f(x)

y0 yn

a b

Luke Cole Page 1


GITIMH3 94107 Integration Page 2

Accurate Integration
Indefinite Integrals:
 The integral of an equation in the form a.x + b is found by

a .x  b n dx  a .x  b   C
n 1
Equation:
 an  1
C = Constant

Definite integrals:

y = a.x + b

c d

d
 a .d  b n 1 a .c  b n 1
Equation:
c
a .x  b  
a n  1 

a n  1 

Even Functions:
 A function is Even if: f( x) = f(x)
a
Equation:
a
f  x dx  0

Odd Functions:
 A function is Odd if: f( x) =  f(x)
a a
Equation:
a
f  x dx  2

0
f  x dx

Luke Cole Page 2


GITIMH3 94107 Integration Page 3

Areas and Volumes


Areas Enclosed by the x-axis:
a b

y = f(x)

b
Equation: A
 f x dx
a

Areas Enclosed by the y-axis:


b
Equation: A
a
f  y dy

a
x = f(y)

Luke Cole Page 3


GITIMH3 94107 Integration Page 4

Volumes about the x-axis:


 Found by rotating as area under a curve about the x-axis

a
y = f(x) b

b
Equation: V 
 a
y 2 dx

Volumes about the y-axis:


 Found by rotating as area under a curve about the y-axis

a
y = f(x)
b

b
Equation: V 
 a
x 2 dy

Area and Volumes between Curves:

 f  y  
b b

  f  x   g  x dx  g  y  2 dx
2
Equation: A V
a a

f(x) = 1st Curve


g(x) = 2nd Curve

Luke Cole Page 4


GITIMH3 94107 Integration Page 5

Integration By Substition
 Used for hard integration

  4
E.g. (1) 3.x 2 x3  1 dx using the substitution u = x3  1

du
A First,  3.x 2
dx
du = 3.x2.dx …(1)
Sub (1) into equation
  5

 4 u5 x3  1
u .du  C  C
5 5


2
E.g. (2) x 1 x using the substitution u = 1+ x2
0

du
A First,  2.x Note:
dx
When, x = 1, u = 2
1
du  x.dx …(1) And, x = 0, u = 1
2
Sub (1) into equation
2 2
1  2.u 3 2 

1 12 2 2 2
u    
2 1 2  3 1 3

Luke Cole Page 5